Volume 2B: Turbomachinery 2018
DOI: 10.1115/gt2018-76450
|View full text |Cite
|
Sign up to set email alerts
|

LES and RANS Analysis of the End-Wall Flow in a Linear LPT Cascade With Variable Inlet Conditions: Part II — Loss Generation

Abstract: In low-pressure-turbines (LPT) at design point around 60–70% of losses are generated in the blade boundary layers far from end-walls, while the remaining 30%–40% is controlled by the interaction of the blade profile with the end-wall boundary layer. Increasing attention is devoted to these flow regions in industrial design processes. Experimental techniques have shed light on the mechanism that controls the growth of the secondary vortices, and scale-resolving CFD have provided a detailed insight into the vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…High-fidelity turbulence eddy resolved (instead of modelled) methods, like large eddy simulation (LES), have been applied to study the endwall flows in the context of low pressure turbine (LPT) cascade [10][11][12]. Turbulence eddy resolved simulations have also been conducted more recently using the DG based methods, typically at relatively low Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%
“…High-fidelity turbulence eddy resolved (instead of modelled) methods, like large eddy simulation (LES), have been applied to study the endwall flows in the context of low pressure turbine (LPT) cascade [10][11][12]. Turbulence eddy resolved simulations have also been conducted more recently using the DG based methods, typically at relatively low Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted using incoming endwall boundary layers with different momentum thicknesses and the endwall vortex characteristics and the associated loss were shown to be considerably affected. The results further revealed that RANS calculations, if performed following strict best practice rules, agreed well with LES, in particular in the prediction of the end wall vortex system, with the only significant differences observed in the loss generation of the blade wake, due to the inability of correctly predicting wake mixing [73]. Ciorciari et al [11] performed a similar investigation in presence of discrete incoming wakes generated with moving bars by running both a set of linear cascade experiments and the companion CFD simulations.…”
Section: Low-pressure Turbinementioning
confidence: 64%
“…5(a), when models with higher additional diffusion coefficients are tested on models with lower additional diffusion coefficients. If models developed on phases which require lower additional diffusion (phases 1-4 & 15-20) are tested on phases which require higher additional diffusion (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), they still reduce the error as they contribute to a fraction of the additional diffusion coefficient required to bring about the maximum possible error reduction.…”
Section: Boundary Layer Physicsmentioning
confidence: 99%
“…Much of the design process for LPTs is, however, conducted using Reynolds-averaged Navier-Stokes (RANS) based turbulence models. Accurate prediction of the wake mixing and other complex phenomena in LPTs is still a challenge for existing RANS models as shown by a number of studies [12][13][14]; and there is plenty of scope for improvement in these models. One of the reasons that RANS closures fail at predicting the turbulent wake mixing with the required degree of accuracy is the use of the Boussinesq approximation [15] for the stress-strain relationship.…”
Section: Introductionmentioning
confidence: 99%